Faktor- Faktor yang Mempengaruhi Perilaku Konsumen terhadap Pembelian Buah-Buahan pada saat Pemberlakuan Pembatasan Kegiatan Masyarakat Darurat di Kota Pontianak - Rindang, Kurnianto; Dolorosa, Eva; Maswadi, Maswadi (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2024)
Consumer behavior is behavior exhibited by people in terms of planning, buying and using economic goods and services. Fruit is a horticultural product that has bright prospects so that it can be developed as a source of economic growth in the agricultural sector.  The CoronaVIrus Disease 2019 (Covid-19) lpandemic lhas lchanged many things such as cleanliness, health and changing human consumption patterns. lSince the lCovid-19 lpandemic entered lIndonesia, the fruits consumption campaign has continued to be intensified. Pontianak City is a city that enforces Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM). Seeing this situation, it is necessary to further investigate how consumer behavior towards purchasing fruits during emergency PPKM. The ldata in lthis study was lsecondary ldata with 133 respondents netted by purposive lsampling lmethod. The lvariables in lthis lstudyl are Cultural, Social, Personal and Psychological. Based on lthe lresults of research using factor analysis, it lcan be concluded lthat the lfactors that influenced consumer behavior towards purchasing fruits during the Imposition of Emergency Restrictions on Community Activities (PPKM) in Pontianak City consisted of 4 factors namely 4 in 1, Psychological, Individual, and Reference and Family. The most dominant factor is the Universal Factor. The indicators included in this factor are Geographic Area, Role and Status, Occupation, Perception, and Confidence and Establishment.